The Speech Act of English and Arabic Racial Memes of Covid19 - Hussein, Dunia Ali (International Journal of Linguistics, 2023)
A meme is a caption image that consists of an image and a witty message which reflects worldwide current incidents. Since the outbreak, Covid19 has received its own share of memes by fueling a pile – on excuses to promote racism on Asian's and particularly the Chinese community as being the major cause of the pandemic. The present study aims to investigate racial memes of (24) English memes and (10) Arabic memes. To achieve this, a pragmatic multimodal approach has been adopted to find answers to the following questions: 1- To what category does the speech act “racialize” belong to? 2- Are racial intentions expressed equally in English and Arabic memes? 3- Is there any difference in the frequency of racial humor in English and Arabic memes? 4- Which category of text – image combination is more frequently used in English and Arabic memes? The findings of the study, show that the speech act of racialize belongs to expressive illocutionary acts since it expresses a negative psychological state of mind and has down face since it is not accepted by everyone. Although, Covid19 memes in English and Arabic sometimes share the same caption and image but the racial intention in English memes are reflected through dark humor unlike Arabic memes which are mostly humorous.